Carbo‐Naphthalene: A Polycyclic carbo‐Benzenoid Fragment of α‐Graphyne. Issue 48 (2nd November 2016) - Cocq, Kévin; Saffon‐Merceron, Nathalie; Coppel, Yannick; Poidevin, Corentin; Maraval, Valérie; Chauvin, Remi
Abstract: A ring carbo ‐mer of naphthalene, C32 Ar8 (Ar= p ‐ n ‐pentylphenyl), has been obtained as a stable blue chromophore, after a 19‐step synthetic route involving methods inspired from those used in the synthesis of carbo ‐benzenes, or specifically devised for the present target, like a double Sonogashira‐type coupling reaction. The last step is a SnCl2 /HCl‐mediated reduction of a decaoxy‐ carbo ‐decalin, which is prepared through successive [8+10] macrocyclization steps. Two carbo ‐benzene references are also described, C18 Ar6 and o ‐C18 Ar4 (C≡C‐Si i Pr3 )2 . The carbo ‐naphthalene bicycle is locally aromatic according to structural and magnetic criteria, as revealed by strong diatropic ring current effects on the deshielding of 1 H nuclei of the Ar groups and on the negative value of the DFT‐calculated NICS at the center of the C18 rings (−12.8 ppm). The stability and aromaticity of this smallest fused molecular fragment of α‐graphyne allows prediction of the same properties for the carbon allotrope itself. Abstract : Towards α‐graphyne : A ring carbo ‐mer of naphthalene, C32 Ar8 (Ar= p ‐ n ‐pentylphenyl), was obtained as a stable blue chromophore in 19 steps. The two carbo ‐benzenes o ‐C18 Ar4 (C≡C−Si i Pr3 )2 and C18 Ar6 are also described. The carbo ‐naphthalene bicycle is locally aromatic according to structural and magnetic criteria. The stability and aromaticity of this smallest fused molecular fragment of α‐graphyne allows prediction of the same properties for the carbon allotrope itself.